Social housing in the Irish housing market - Eoin Corrigan; Dorothy Watson (The Economic and Social Research Institute (ESRI), 2018)
This working paper traces the evolution of social supports for housing since 2004, including local authority (LA) housing, housing provided by Approved Housing Bodies (AHB) and support for renting in the private sector through schemes administered by the local government sector (Rental Accommodation Scheme (RAS) and the Housing Assistance Payment (HAP)) and the Rent Supplement scheme operated by the Department of Employment Affairs and Social Protection. Given the increased use of the private sector to provide housing for low-income households, the paper draws on SILC data to examine changes between 2004 and 2015 in the quality of housing in different sectors, as measured by problems such as dampness, lack of central heating, lack of double glazing, insufficient light and noise. The main findings are: The overall percentage of housing that is socially supported increased during the recession to 17% from 13% in the boom years (2004-2007, mainly via increased use of Rent Supplement) but dropped back towards pre-recession levels by 2015 (about 15%).Growth in use of the private sector for socially-supported housing rose from 28% in the boom years to 42% during the recession before dropping back to 33% by 2016. Housing quality improved between 2004 and 2015, with a drop from 16% to 9% in the percentage of people living in dwellings with 2 or more of the five quality problems; The improvements were significantly greater for those living in rented than owned/mortgaged dwellings, though rented dwellings remained at a disadvantage in 2015; Improvements in quality in the rented sector were found across the income distribution.
Keywords: 330